Joint Rhythmic Movement Increases 4-Year-Old Children’s Prosocial Sharing and Fairness Toward Peers - Rabinowitch, Tal-Chen; Meltzoff, Andrew N. (Frontiers in Psychology, 2017)
The allocation of resources to a peer partner is a prosocial act that is of fundamental importance. Joint rhythmic movement, such as occurs during musical interaction, can induce positive social experiences, which may play a role in developing and enhancing young children’s prosocial skills. Here, we investigated whether joint rhythmic movement, free of musical context, increases 4-year-olds’ sharing and sense of fairness in a resource allocation task involving peers. We developed a precise procedure for administering joint synchronous experience, joint asynchronous experience, and a baseline control involving no treatment. Then we tested how participants allocated resources between self and peer. We found an increase in the generous allocation of resources to peers following both synchronous and asynchronous movement compared to no treatment. At a more theoretical level, this result is considered in relation to previous work testing other aspects of child prosociality, for example peer cooperation, which can be distinguished from judgments of fairness in resource allocation tasks. We draw a conceptual distinction between two types of prosocial behavior: resource allocation (an other-directed individual behavior) and cooperation (a goal-directed collaborative endeavor). Our results highlight how rhythmic interactions, which are prominent in joint musical engagements and synchronized activity, influence prosocial behavior between preschool peers.